Kepemimpinan Pendidikan Berbasis Uswatun Hasanah: Menjadikan Kepala Sekolah sebagai Role Model Karakter di Era Digital - Siswadi, Siswadi (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
The world of education is currently undergoing a massive digital transformation that is not only changing learning methods but also shifting the values ​​and ethics within the school environment. The character crisis, such as cyberbullying and the degradation of morality, demands the emergence of leaders capable of serving as moral compasses amidst technological disruption. This study aims to explore the actualization of the Uswatun Hasanah concept by school principals as a character-strengthening strategy in the digital era. The research method used was qualitative with a library research approach. Data were collected through relevant literature, including the Quran (specifically Surah Al-Ahzab: 21), books, and research journals on digital education transformation. The results indicate that Uswatun Hasanah-based leadership positions the principal's personal integrity as a "living curriculum." Recontextualizing this concept within modern management includes the application of authentic leadership, transparency, and professionalism (Ihsan). In the digital era, principals serve as role models through ethical communication in cyberspace, wisdom in managing digital footprints, and strengthening digital empathy. The implementation of these values ​​aims to create a school ecosystem that is Rahmatan Lil 'Alamin (Rahmatan Lil 'Alamin)—an inclusive, safe environment that serves as a source of goodness for all school members amidst the tide of disruption. This study concludes that the key to successful character education in the digital age lies not in technological sophistication, but rather in the depth of integrity and exemplary behavior of the leader.